1997
DOI: 10.1095/biolreprod57.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxanthine Regulation of Oocyte Maturation in the Mouse: Insights Using Hypoxanthine Phosphoribosyltransferase-Deficient Animals1

Abstract: In this study the effects of hypoxanthine (HX) on meiotic maturation were compared using oocytes from mice possessing a hypoxanthine phosphoribosyltransferase null mutation (HPRT-) and from the corresponding HPRT-competent background strain (HPRT+). Oocyte-cumulus cell complexes and cumulus cell-enclosed oocytes (oocytes cultured while enclosed by cumulus cells) from HPRT+, but not HPRT-, mice took up HX and contained significant levels of HPRT activity. In addition, FSH increased, and HX suppressed, the de no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Therefore, FSH may trigger an alternative pathway that can decrease or bypass the high intracellular concentration of cGMP and consequently also cAMP in oocytes. It has been shown that FSH can trigger meiotic resumption in mammalian oocytes inhibited at the GV stage by drugs increasing the intracellular concentration of cAMP, like hypoxanthine [ 40 ], dibutyryl cAMP [ 41 ] or PDE3A inhibitors [ 42 ] via a mechanism involving the protein kinase C and EGFR/MAPK3/1 pathways [ 41 , 43 , 44 ]. Moreover, the cGMP analogues are probably hydrolyzed in the COCs by cGMP-specific phosphodiesterases, the activity of which may be affected by FSH.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, FSH may trigger an alternative pathway that can decrease or bypass the high intracellular concentration of cGMP and consequently also cAMP in oocytes. It has been shown that FSH can trigger meiotic resumption in mammalian oocytes inhibited at the GV stage by drugs increasing the intracellular concentration of cAMP, like hypoxanthine [ 40 ], dibutyryl cAMP [ 41 ] or PDE3A inhibitors [ 42 ] via a mechanism involving the protein kinase C and EGFR/MAPK3/1 pathways [ 41 , 43 , 44 ]. Moreover, the cGMP analogues are probably hydrolyzed in the COCs by cGMP-specific phosphodiesterases, the activity of which may be affected by FSH.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many of the experiments showing successful meiotic induction during coculture have been carried out using hypoxanthine as the meiotic inhibitory agent. Studies demonstrating active uptake of this purine base by oocyte-CC complexes (Downs et al, 1986;Downs, 1994Downs, , 1997 raise the possibility that its sequestration by CCs reduces the inhibitory potency of the medium during coculture, leading to higher maturation percentages. In fact, one possible explanation for the lack of an inhibitory effect of conditioned hypoxanthinesupplemented medium on the maturation of CEO is that consumption of hypoxanthine by CEO during conditioning offset any negative influence that was generated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Acacb −/− mice show normal fertility, suggesting that there is some redundancy of function wherein ACACA produces enough malonyl CoA to dampen FAO and premature meiotic resumption. The line of Acacb −/− mice used in this study overexpress hypoxanthine‐guanine phosphoribosyltransferase (Abu‐Elheiga et al, ), but this cannot account for the effects seen on meiosis and FAO because increased levels of this enzyme would be expected to produce effects opposite to those observed (Downs, ).…”
Section: Discussionmentioning
confidence: 99%